1996
DOI: 10.1097/00005344-199601000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Endothelin-B Receptors in Atherosclerotic Human Coronary Arteries

Abstract: Both endothelin-A (ETA) and endothelin-B (ETB) receptors are known to be present in human coronary arteries. However, their absolute and relative amounts, functional roles, and the influence of pathology are uncertain. The goal of the present study was to characterize endothelin receptors mediating constriction in human coronary arteries and to assess the influence of cardiomyopathy (CMP) and coronary artery disease (CAD) on ET receptors in human tissue. For comparison, porcine coronary arteries were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
84
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(95 citation statements)
references
References 39 publications
9
84
1
1
Order By: Relevance
“…In diet-induced hypercholesterolemia and atherosclerosis, there is diffuse upregulation of the ETB receptor. 28,29 Furthermore, we 30 showed that in a canine experimental model of heart failure, which is associated with endothelial dysfunction, there is enhanced coronary vasoconstriction to ETB-receptor activation, albeit primarily at the level of the coronary microcirculation. It is thus possible that the contribution of endogenous ET to acetylcholine-induced coronary epicardial vasoconstriction in hypercholesterolemia is primarily mediated by ETB receptors, rather than by ETA receptors.…”
Section: Discussionmentioning
confidence: 95%
“…In diet-induced hypercholesterolemia and atherosclerosis, there is diffuse upregulation of the ETB receptor. 28,29 Furthermore, we 30 showed that in a canine experimental model of heart failure, which is associated with endothelial dysfunction, there is enhanced coronary vasoconstriction to ETB-receptor activation, albeit primarily at the level of the coronary microcirculation. It is thus possible that the contribution of endogenous ET to acetylcholine-induced coronary epicardial vasoconstriction in hypercholesterolemia is primarily mediated by ETB receptors, rather than by ETA receptors.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the importance of ETB receptors in pathological situations may be reflected by enhanced receptor densities as recently described for the aorta of spontaneously hypertensive rats [9], the basilar artery of rabbits after subarachnoidal hemorrhage [11] and for the rabbit carotid artery after balloon denudation [29]. Most recently, an upregulation of ETB receptors has also been demonstrated in human coronary arteries from atherosclerotic patients [10]. In order to further characterize the nature of these ETB receptors and to clarify the role of ETB receptors in pathology, ETB receptor selective antagonists are an essential tool.…”
Section: Discussionmentioning
confidence: 82%
“…Unfortunately, so far no data with corresponding human constricting ETB receptors are available. Efforts to measure sarafotoxin $6c mediated constriction in human atherosclerotic coronary arteries failed due to the occurrence of spontaneous phasic constrictions [10]. However, because similar binding potency and selectivity ratio was found between human and rat ETA and ETB receptors, Ro 46-8443 seems to display few if any species differences, suggesting a highly conserved binding site on the ET receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with hypertension have increased endothelin receptor activity and an increased vascular tone (Li et al, 2007). The atherosclerotic arteries exhibit a similar receptor upregulation (Dagassan et al, 1996;Pernow et al, 2000), suggesting that this receptor upregulation takes place during pathological conditions. In human atherosclerotic lesions, there is also an increase in 18 ET-1 and ET B receptors and this increase is seen in the medial VSMC, just beneath the foam cells (Iwasa et al, 1999).…”
Section: Upregulation Of Vascular Endothelin Receptorsmentioning
confidence: 99%